Kontribusi Wanita Tani Pada Usaha Tani Cabai Rawit - , Novi Nurhayati; Risca Permatasari; Dwi Tri Nilasari (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
The cayenne pepper plant commodity is a strategic agricultural commodity, has high economic value and a wide market share. The cultivation of cayenne pepper plants in West Kotawaringin Regency is generally carried out by farming households. A farming household is a group of people who live in part or all of a building and generally eat together from one kitchen with the head of the household working in the agricultural sector. The formulation of the problem in this research is whether the workforce in cayenne pepper farming is experiencing a shift to female farming workforce. In answering the research objective "to identify whether there is a shift in agricultural work among women farmers" using qualitative descriptive methods. In cayenne pepper farming in South Arut District, cayenne pepper farmers use male labor and female labor. The number of female workers used is 53.48% of all existing activities. In general, the number of hours women work in farming is more, but these women farmers work only in certain processes that do not require a lot of physical effort, such as the harvesting process, the irrigation process, the planting process, caring for seeds, additional fertilization, planting and sowing.